Peran Budaya Religius Madrasah dalam Pengembangan Karakter Spiritual Siswa di MAN 1 Bukittinggi - Jannah, Nadila Miftahul; Syawaluddin, Syawaluddin (Al-DYAS, 2023)
Madrasah religious culture is the realization of the value of religious teachings as a tradition in behavior and organizational culture which is followed by all madrasah residents. In the religious culture of this madrasah, one can see how the spiritual character of students who carry out this religious culture every day can be seen. This study aims to (1) describe the religious culture of the madrasa, (2) describe the spiritual character of students, (3) and reveal the role of the religious culture of the madrasa in developing the spiritual character of students. This type of research is qualitative research in which observations and interviews are conducted with homeroom teachers, guidance and counseling teachers, and teachers from the coordinator of religion at MAN 1 Bukittinggi. The data that has been collected from the sources is then carried out data reduction and data verification regarding the role of madrasah religious culture in developing the spiritual character of students at MAN 1 Bukittinggi. Because with the religious culture of the madrasa it can develop the spiritual character of students at MAN 1 Bukittinggi.